A rapid and naked-eye methicillin resistant Staphylococcus aureus screening method based on CRISPR/Cas12a and hybridization chain reaction - Jiang, Yayun; Chen, Zongyao; Liu, Xiao; Xin, Qi; Wang, Dengchao; Ji, Caixia; Li, Youwei; Mai, Gang (Frontiers in Microbiology, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA), a widely drug-resistant bacterium, poses a significant threat to global health. Current culturing and nucleic acid detection methods are time-consuming and require complex instruments, which do not meet the detection needs. Herein, we developed a rapid and visual MRSA detection method (MCFHCR) using ssDNA-functionalized magnetic beads as a trigger chain combined with the trans-cleavage activity of the Cas12a protein and fluorescence signal amplification of the hybridization chain reaction (HCR). MCFHCR is a signal-off platform for the detection of MRSA. In the absence of DNA targets, the trans-cleavage activity of Cas12a is inactivated, allowing HCR to proceed and form long double-stranded DNA, resulting in an increased fluorescent signal. In the presence of the DNA targets, the trans-cleavage activity of CRISPR/Cas12a is activated to cleave the trigger strand, failing HCR and leading to a decrease in the fluorescence signal. Combined with RPA, MCFHCR was completed within 35 min, achieving a limit of detection (LOD) of five copies/μL for mecA DNA and 8 CFU/mL for MRSA. In detecting clinical strains, MCFHCR demonstrated comparable performance to qPCR and drug sensitivity testing. Therefore, with its simple, rapid operation and convenient signal acquisition, MCFHCR shows significant practical applicability in detecting MRSA.